PERSEPSI WISATAWAN PASCA RELOKASI PEDAGANG KAKI LIMA DI KAWASAN MALIOBORO KOTA YOGYAKARTA - Quamilla Nugroho, Sarah; Akiriningsih, Titik; Pradipta, Made Prasta Yostitia (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2024)
The relocation of hawkers in Malioboro area has an impact on various parties, especially tourist who visit Malioboro area. This change has an impact on tourists’ perception towards Malioboro area. Therefore, this research aims to determine the perception of tourists regarding the ambiance in Malioboro area after the relocation of the hawkers based on the satisfaction of tourist visits and to determine accessibility, facilities, and environment in Malioboro area after the relocation of the hawkers. This research applied descriptive research method with quantitative approach. The population in this research is tourist who have visited the Malioboro area before and after the relocation of hawkers with a sample of 100 respondents. The data were collected using questionnaires, observations, and interviews. There are 3 variables used to measure tourist perceptions, which are Accessibility, Facilities, Environment. The characteristics of tourists are dominated by female tourists with an age range of 20-29 years old, mainly from Central Java. And the result of data analysis shows that 25% of tourists give their perception of the environment of Malioboro area before the relocation of the hawkers and 31% of tourists give their perception of the environment of Malioboro area after the relocation of the hawkers. This study concluded that the perception of tourists is dominated by tourists who agree with the Malioboro area after the relocation of the hawkers.